Psychosocial factors related to physical activity in frail and prefrail elderly people - Fabio Jiménez-Zazo (BMC Geriatrics, 2022)
Abstract Background Increased physical activity (PA) is a very important factor in a healthy aging lifestyle. Psychosocial factors have also a main role in the initiation and maintenance of this behavior, but nowadays its implications for frailty elderly people are unknown, therefore, the aim of this study was to identify the psychosociological variables of behavior change that influence the practice of (PA) in frail and prefrail elderly. Methods A total of 103 frail and pre-frail elderly people (72 females) participated in this cross-sectional study, on the framework of the EXERNET-Elder3.0 project. Age ranged from 68–94 years (mean = 80.4 ± 5.9 years). Individualized face-to-face interviews according to the constructs of the Transtheoretical Model of Change (TTM) [(decisional balance (DB) and self-efficacy (SE)], social support (SS) (family and friends) and outcome expectations (OE) were administered to all participants. Results Significant differences were found in DB, perceived benefits (PBn), SE, family-related SS and OE as a function of stages of change (SoC) (p < 0.005), but no significant were found in perceived barriers (PBrr) (p = 0.259) and friends-related SS (p = 0.068). According to the Scheffé post-hoc test, those in advanced SoC (Action-Maintenance), scored higher than those in lower SoC (Precontemplation-Contemplation and Preparation). Conclusion The scores obtained from the study variables differed according to the SoC, supporting the external validity for the use of the TTM in frailty elderly. Further research is needed to determine the impact of PBrr and friends-related SS on this people, as well as to identify the validity of this model in the long-term in this population.